Human resource management and economic success: An Australian perspective - Peter J. Dowling (Management Revue, 2005)
In this paper we examine the case for a link at the national and firm level between human resource management (HRM) and economic success in Australia. A brief history of the industrial development of Australia (and New Zealand) is presented and some differentiating factors noted (Dowling/Boxall 1994). A key factor with regard to Australia is the relatively small size of the population and economy and the disproportionate impact of globalisation and global political and economic events upon the performance of the Australian economy. Recent empirical research in the US which argues that there is evidence that positive employee relations effectively serves as an intangible and enduring asset at the firm level (Fulmer/Gerhart/Scott 2003) is noted, as is the December 2003 special issue of International Journal of Human Resource Management which focuses on Developments in Comparative HRM and concludes that there is evidence both for and against the hypothesis that there are no universal prescriptions for effective HRM. The editors (Wright and Brewster) argue that 'the variety of views about what makes for 'good HRM' and the variety of understandings of which policies and practices lead to success is not only inevitable, but should be welcomed' (Wright/Brewster 2003: 1305). The author is in broad agreement with this conclusion.
Keywords: 650; HRM; Australian perspective; firm performance; economic success; German companies operating in Australia; Personalmanagement; Betriebsklima; Unternehmenserfolg; Multinationales Unternehmen; Deutsch; Australien